2013
DOI: 10.9734/bjmmr/2013/2650
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Endoscopic, Pathological and Serological Findings of Helicobacter pylori Infection in Saudi Patients with Upper Gastrointestinal Diseases

Abstract: Author MAA planned and designed the study, wrote the protocol, participated in the interpretation of the results and analysis, drafted and critically revised the manuscript for important intellectual content and approval of the version to be published. Author TAE participated in planning and designing the study, sample collection and drafting of the manuscript. Author MSA collected the data and performed the practical laboratory activities. All authors also read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…This study showed that H. pylori infection was diagnosed in 72.8% of the studied patients. prevalence of infection in our study is comparable to that found in a Saudi study conducted by Abo-Shadi et al [1], where H. pylori infection was detected in 64.7% of the gastric biopsy specimens from patients with upper gastrointestinal diseases. The prevalence found in our study lies within the wide range of H. pylori infection (50-80%) reported in Saudi Arabia [5].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that H. pylori infection was diagnosed in 72.8% of the studied patients. prevalence of infection in our study is comparable to that found in a Saudi study conducted by Abo-Shadi et al [1], where H. pylori infection was detected in 64.7% of the gastric biopsy specimens from patients with upper gastrointestinal diseases. The prevalence found in our study lies within the wide range of H. pylori infection (50-80%) reported in Saudi Arabia [5].…”
Section: Discussionsupporting
confidence: 90%
“…In a study from Mumbai, age related prevalence of Helicobacter pylori showed similar results as ours with maximum prevalence of 58% in the age group of 30-39 years 36 . Our study revealed that there was not a correlation between sex and H. pylori positivity (P=0.982, this result is in agreement with study performed by (AboShadi et al) 37 , but disagree with other studies (AAmeri and Alkadasi) 29 .…”
Section: Discussionsupporting
confidence: 78%
“…Another study in the same country done by Abo-shadi et al [16] showed that H. Pylori infection was detected in 64.7% of the gastric biopsy specimens from patients with upper gastrointestinal diseases.…”
Section: Discussionmentioning
confidence: 87%